Numerical simulations of macrospicule jets under energy imbalance conditions in the solar atmosphere - González-Avilés J.J.; Murawski K.; Srivastava A.K.; Zaqarashvili T.V.; González-Esparza J.A. (My University, 2025)
Using numerical simulations, we study the effects of thermal conduction and radiative cooling on the formation and evolution of solar jets with some macrospicules features. We initially assume that the solar atmosphere is rarely in equilibrium through energy imbalance. Therefore, we test whether the background flows resulting from an imbalance between thermal conduction and radiative cooling influence the jets' behaviour. In this particular scenario, we trigger the formation of the jets by launching a vertical velocity pulse localized at the upper chromosphere for the following test cases: (i) adiabatic case; (ii) thermal conduction case; (iii) radiative cooling case; and (iv) thermal conduction + radiative cooling case. According to the test results, the addition of the thermal conduction results in smaller and hotter jets than in the adiabatic case. On the other hand, the radiative cooling dissipates the jet after reaching the maximum height (≈5.5 Mm), making it shorter and colder than in the adiabatic and thermal conduction cases. Besides, the flow generated by the radiative cooling is more substantial than that caused by the thermal conduction. Despite the energy imbalance of the solar atmosphere background, the simulated jet shows morphological features of macrospicules. Furthermore, the velocity pulse steepens into a shock that propagates upward into a solar corona that maintains its initial temperature. The shocks generate the jets with a quasi-periodical behaviour that follows a parabolic path on time-distance plots consistent with macrospicule jets' observed dynamics. © 2021 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.